Princípios para uma proposta de trabalho com narrativa no ensino fundamental - Ramos, Sirlene Borges da Silva (2023)
This work's main objective is to present a reflection on the production of narratives, based on theoretical-methodological principles derived from Bakhtinian studies on exotopy and chronotope, in view to propose a working with narrative in Elementary Education in the light of Bakhtinian theory. The object of study consisted of four narratives that are part of the book My stories are your stories: what we feel about isolation? (Minhas histórias são suas histórias: o que sentimos com o isolamento?), by Luciana Savaget (2021). According to Bakhtin (1997), language is formed by statements and they will reflect specific conditions for the purposes of each field, not only due to its theme and language style used. Thus, the investigative question was: what theoretical-methodological principles underlie the reflection on narratives produced in the work My stories are your stories: what we feel about isolation? Methodologically, the study adopted bibliographical research procedures, with narrative analysis based on two Bakhtinian principles: 1) the exotopic and 2) the chronotope. The narratives analyzed highlighted the narrator's view of time and space, as well as the environment influence on writing, in addition to the propagation of new habits assumed as fixed postures in human action based on experiences and measures adopted to guarantee safety. It was concluded that the narratives are constituted from the multiple and dialogical look of the authors - exotopic - on the object or event narrated and the construction of time combined with the space of the narrative - chronotope - so that the constructions can give meaning to the entire text, providing an important discussion when considering the action of narrating an experienced moment